COMMUNITY EMPOWERMENT FOR PHYSICAL DISABILITIES THROUGH THE INDEPENDENT GROWING FARMERS GROUP (TUMAN) DPC-PPDI CIMAHI CITY - Komarudin, Danti; Yuningsih, Yuyun (Universitas Pasundan, 2025)
Study This entitled